Validation of Tanaka and Johnston Method on Iraqi Population - Hind T Jarjees; Khawla M Awni; Younis MS Hasan (University of Mosul, College of Dentistry, 2009)
Aims: To validate Tanaka and Johnston's analysis on (50) Iraqi patients (29 females and 21 males)aged 14-22 years. The patients had normal class I molar relation ship with full permanent dentition.Materials and Methods: Plaster models of 50 (14-22) years old patients were selected. Mesio-distalcrown diameter for maxillary and mandibular permanent teeth were measured. Statistical descriptive,probability theory, correlation coefficients between individual and grouped teeth were calculated usingTanaka and Johnston method. Results: Tanaka and Johnston's analysis tables, equations and approximationswere modified in order to improve the accuracy of the prediction. The correlation coefficientsfound between the size of the permanent mandibular central incisors and maxillary first molars (1, 1, 6and 6) and maxillary and mandibular canines and premolars were high (r = 0.62 and r = 0.67, respectively).New, more accurate prediction tables applicable at earlier ages, and new regression equationswere constructed. In addition, new easier approximations were developed to allow the prediction of thesize of the unerupted maxillary canines and premolars by adding 5.6 mm to the half-widths of teeth 1,1, 6 and 6. The analogous prediction of the size of unerupted mandibular canines and premolars wasobtained by adding 5.4 mm to the half widths of same teeth 1 ,1 , 6 and 6. Conclusions: The new analysisprediction tables and new regression equations based on teeth 1 ,1, 6 and 6, which erupt earlierthan teeth used by Tanaka and Johnston, proved even more accurate than both previous equations.